2009
DOI: 10.1021/es802400y
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Bromination and Evaporation of Zinc Oxide during Thermal Treatment with TBBPA

Abstract: Thermodynamic considerations indicate that base metal oxides such as ZnO, PbO, Cu2O, etc. should easily react with HBr, the main gaseous product from the thermal decomposition of tetrabromobisphenol A (TBBPA), to form low boiling point metallic bromides suitable for volatile separation. In this work a differential scanning calorimeter and laboratory-scale furnace was used to investigate the scope and conditions for the bromination of ZnO by the thermal decomposition of TBBPA. The formed solid, condensed, and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 17 publications
2
17
0
Order By: Relevance
“…The evidence of char formation during the thermal decomposition of pure TBBPA was confirmed in many studies [8][9][10]25]. However, it was also found that the presence of some halide metals (SbCl 3 , ZnBr 2 ) [5,28] and (SbOCl) [28] may enhance char formation.…”
Section: Temperature Of 390 8cmentioning
confidence: 66%
See 1 more Smart Citation
“…The evidence of char formation during the thermal decomposition of pure TBBPA was confirmed in many studies [8][9][10]25]. However, it was also found that the presence of some halide metals (SbCl 3 , ZnBr 2 ) [5,28] and (SbOCl) [28] may enhance char formation.…”
Section: Temperature Of 390 8cmentioning
confidence: 66%
“…For these materials, hydrobromic acid (HBr) must be released as a product of decomposition of BFR plastics during pyrolysis [4]. We have suggested in a previous paper, the possibility of a volatile separation of metallic compounds such as zinc oxide (ZnO) in the waste by the HBr released from the tetrabromobisphenol A (TBBPA) decomposition [5].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Vasile et al (2007) used computer scrap, i.e., PCBs, casings, and keyboards, to produce oil and high aromatic fraction content in liquid oil. Furthermore, it is possible that bromobisphenol A and brominated bromobisphenol A (2.3-10%) were found in the liquid product because they did not completely decompose during the pyrolysis process (Barontini et al 2004b;Barontini et al 2005;Grabda et al 2009). But the bromobisphenol A and brominated bromobisphenol A species contents in liquid product were low or at trace levels in GC-MS spectra of liquid product in this study.…”
Section: Element Compositionsmentioning
confidence: 99%
“…A thermodynamic consideration suggests that base metal oxides including ZnO, PbO and Cu 2 O react readily with HBr originating from degradation of TBBA [13]. Recent study by Grabda et al showed that the bromination of zinc took place in the simultaneous heat treatment of the mixture of TBBA and ZnO [14]. In the present work we have examined the influence of variety of metal oxides, namely ZnO, Fe 2 O 3 , La 2 O 3 , CuO and CaO, on the thermal degradation of TBBA.…”
Section: Introductionmentioning
confidence: 99%